Proceedings of the 27th ACM SIGKDD Conference on Knowledge Discovery &Amp; Data Mining 2021
DOI: 10.1145/3447548.3467224
|View full text |Cite
|
Sign up to set email alerts
|

Learning to Recommend Visualizations from Data

Abstract: Visualization recommendation is important for exploratory analysis and making sense of the data quickly by automatically recommending relevant visualizations to the user. In this work, we propose the first end-to-end ML-based visualization recommendation system that leverages a large corpus of datasets and their relevant visualizations to learn a visualization recommendation model automatically. Then, given a new unseen dataset from an arbitrary user, the model automatically generates visualizations for that n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 32 publications
(32 reference statements)
0
5
0
Order By: Relevance
“…Various researchers have implemented the Likert scale to evaluate data in a visualization system Islam et al 97 The Likert scale is popular in survey research because it allows personality traits or perceptions to be operationalized quickly. For example, in 2020, Qian et al 64 proposed the first end-to-end graphical recommendation system based on ML. They formalized and described a generic learning framework to solve the problem of ML-based visualization recommendations and used trained models to automatically generate, and evaluate a list of recommended views for new data sets which are unknown to arbitrary users.…”
Section: Overview Of Evaluation Methods and Terminology: State-of-the...mentioning
confidence: 99%
See 1 more Smart Citation
“…Various researchers have implemented the Likert scale to evaluate data in a visualization system Islam et al 97 The Likert scale is popular in survey research because it allows personality traits or perceptions to be operationalized quickly. For example, in 2020, Qian et al 64 proposed the first end-to-end graphical recommendation system based on ML. They formalized and described a generic learning framework to solve the problem of ML-based visualization recommendations and used trained models to automatically generate, and evaluate a list of recommended views for new data sets which are unknown to arbitrary users.…”
Section: Overview Of Evaluation Methods and Terminology: State-of-the...mentioning
confidence: 99%
“…Qian et al 64 Likert Scale 7 point Likert scale accurately identified the highest scoring ML-based visualization recommender system according to the human expert's ratings It failed to measure the actual attitudes of respondents as only a few are rated efficiently rather than all users.…”
Section: Advantages Disadvantagesmentioning
confidence: 99%
“…Visualization recommendation techniques focus on automatically generating proper and desired visualizations for data analysts to explore data and discover insights [67]. Many previous studies adopt rule-based [34,35,40,61] and learning-based [7,20,31,33,38,42] approaches to suggest visual encodings of specified data based on data attributes, tasks, and visual perception theory. Moreover, other work [5,26,32,43,57,60,62] builds interactive systems that utilize visualization recommendations to facilitate data exploration.…”
Section: Visualization Recommendation For Data Analysismentioning
confidence: 99%
“…A corpus of research has been proposed on generating single visualization [19], [37], [42] or multiple-view visualizations [11]. Typically, these studies deal with data table queries, outputting static visualizations.…”
Section: Insights Recommendation In Visual Analyticsmentioning
confidence: 99%